Children's Anxiety At Children's Daycare Park - Utami, Wiwik; Sari, Suci Arsita; Susanti, Dwi Agung (Sean Institute, 2022)
Child Care Park is one of the ways that many parents choose so that their children can continue to receive good education and care while parents are busy working. However, when children first adapt to the school environment, there are 2 child behaviors that appear, namely children can adapt or adjust and children experience anxiety in the form of fussy children, crying and not wanting to be left in the TPA. The purpose of the study was to identify the anxiety of children in day care. Descriptive research design, survey approach. The population is all parents of children in the Bojonegoro City Child Care Park in 2022 as many as 123 people, a sample of 25 respondents was obtained by purposive sampling technique. The research variable is anxiety in children at the Daycare Park. The instrument uses a questionnaire. Data processing by editing, coding, scoring, tabulating and descriptive data analysis with percentages. The results showed that most of the children in daycare did not experience anxiety, as many as 25 children (84%). Children do not experience anxiety while in Daycare if the mother is able to respond to the child's attitude, is more flexible in applying discipline to the child and does not limit the child's desire to learn something he likes. Efforts in preventing and overcoming anxiety in children while in the Daycare Park are by providing information to mothers who should be able to keep their promises to their children.